Studi Teks Lontar Nerang Ujan - Putu Eka Sura Adnyana; Ni Nyoman Suryani (Sphatika: Jurnal Teologi, 2023)
This text study paper of lontar nerang ujan uses the theory of semiotics and transcendental communication. The method used in data collection uses the listening method combined with the basic technique of note taking. The Lontar Nerang Ujan text explains several ways to eliminate rain, and make the sky clear again, by combining script, mantra and banten means, besides that it also explains how to bring rain/make it rain with spells and means that are slightly different from how to stop the rain. The use of banten in stopping rain or bringing rain is a form of devotion of the rain handler to God Almighty who is in charge of the universe, with the aim of making the procession of Panerang Ujan or Pangujanan easier and smoother. The procedure of a rain handler must understand the philosophical script and the use of Balinese script in rerajahan, the concept of gods in the procession of nerang ujan or pangujanan, understand the mantras that are chanted and the use of facilities for the procession of nerang ujan or pangujanan.